Optimalisasi Manajemen Program 1.000 Hari Pertama Kehidupan (HPK) : Intervensi Gizi Melalui Edukasi Berbasis Komunitas di Wilayah Pedesaan - Rasidar, Rasidar; Anwar, Hairil; Marini, Marini; Aprianto, Didik; Hardilina, Hardilina (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Malnutrition is still a serious challenge in rural areas of Indonesia, including in Penibung Village, Mempawah Hilir District. The impacts include physical growth, cognitive development, and overall quality of life. This Community Service (PKM) activity aims to increase public understanding and awareness of the importance of balanced nutrition through interactive education based on the Participatory Action Research (PAR) approach. The activity was carried out using a participatory counseling method involving housewives and integrated health post cadres. The material includes an introduction to macro and micro nutrition, the short and long-term impacts of malnutrition, and the importance of fulfilling nutrition in the first 1,000 days of life (HPK). The evaluation showed an increase in participant knowledge by 35% based on the post-test results, as well as the emergence of behavioral changes in managing family diets. These results indicate that dialogic and visual-based counseling is effective in building nutritional awareness at the community level and is worthy of being replicated sustainably.